Cartels, managerial incentives, and productive efficiency in German coal mining, 1881-1913 - Carsten Burhop; Thorsten Lübbers (Max Planck Institute for Research on Collective Goods, 2008)
In this paper, we evaluate the impact of cartelisation and managerial incentives on the productive efficiency of German coal mining corporations. We focus on coal mining in the Ruhr district, Germany's main mining area. We use stochastic frontier analysis and an unbalanced dynamic panel data set for up to 28 firms for the years 1881-1913 to measure productive efficiency. We show that coal was mined with decreasing returns to scale. Moreover, it turns out that cartelisation did not affect productive efficiency. Controlling for corporate governance variables shows that stronger managerial incentives were significantly correlated with productive efficiency, whereas the debt-equity ratio did not influence it.
Keywords: N53; L41; L71; 330; Economic history; Germany pre-1913; Cartel; Productive efficiency; Corporate Governance; Corporate Governance; Führungskräfte; Leistungsorientierte Vergütung; Kartell; Kohlenbergbau; Technische Effizienz; Geschichte; Deutschland (bis 1945)